Analisis jaringan jalan hutan dan manfaatnya bagi beaya pengusahaan hutan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The purpose of this research were to find out the road density in Perhutani (Forest State Enterprise) Unit I Central Java